Scientific Article Review Project in Professional Education Lectures: Developing the Competence of Prospective High School Physics Teachers with the Project-Based Learning Model - hikmawati, hikmawati; Busyairi, Ahmad; Nisrina, Nina (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2024)
The application of the Project-Based Learning (PjBL) model in the Education Profession course aims to develop the competence of prospective high school physics teacher students. This study uses a case study design with 28 class IIA students in the even semester of 2024 in the Physics Education Study Program, FKIP, University of Mataram as subjects. Data were obtained through a learning outcome test in the form of 10 descriptive questions which were analyzed to see individual and classical completeness. Individual completeness is achieved if the student's score is above 75.0 and classical completeness is achieved if 85% of students get a score above 75.0. The results of the study showed an average score of 85.2 with 100% of students meeting the individual and classical completeness criteria. These findings indicate that PjBL is effective in improving the competence of prospective physics teacher students through scientific article review activities. In other words, student competencies have been successfully developed through the application of the PjBL model. The scientific article review project has developed critical and analytical thinking skills needed by students to support 21st century learning. The implementation of PjBL in this course is not only relevant to the vision of the Physics Education Study Program to produce professional graduates, but also supports the achievement of national education goals. This study recommends the implementation of PjBL in other courses and the development of further research related to its effectiveness in improving the innovative skills of prospective teacher students.